PENGARUH POLA ASUH PERMISIF TERHADAP KEMANDIRIAN ANAK USIA 4-5 TAHUN (Penelitian Kuntitatif Ex-post Facto di Desa Puser, Serang-Banten) - Evitasari Evitasari; Siti Khosiah; Tri Sayekti (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2021)
This study aims to determine the effect of permissive parenting on the independence of children aged 4-5 years in Puser Village, Tirtayasa District, Serang- Banten. The method used in this research is the Expost Facto method with a quantitative approach. The population in this study amounted to 66 children and parents. The number of samples taken based on total sampling technique, namely 66 children and parents in Puser Village, Tirtayasa District, Serang-Banten. Data collection techniques using a likert scale. Testing the validity and reliability of the instrument, normality test, and hypothesis testing were processed with the help of the SPSS 22.0 for windows program. Based on the results of the study it can be concluded as follows, there is a positive and significant effect of permissive parenting on the independence of children aged 4-5 years in Puser Village, Tirtayasa District, Serang-Banten. This can be seen from the significant value obtained, namely 0,000 < 0.05, which means that H1 is accepted and H0 is rejected. So it can be concluded that there is a significant effect of permissive parenting on the independence of children aged 4-5 years in Puser Village, Tirtayasa District, Serang- Banten.